2016
DOI: 10.1016/j.neuroscience.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

GABA levels in the ventromedial prefrontal cortex during the viewing of appetitive and disgusting food images

Abstract: Characterizing how the brain appraises the psychological dimensions of reward is one of the central topics of neuroscience. It has become clear that dopamine neurons are implicated in the transmission of both rewarding information and aversive and alerting events through two different neuronal populations involved in encoding the motivational value and the motivational salience of stimuli, respectively. Nonetheless, there is less agreement on the role of the ventromedial prefrontal cortex (vmPFC) and the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…This is an important finding for studies that hypothesise a low concentration change in GABA. However, for an effect size of around 15%, we predict much more reasonable sample sizes (between 8 and 43 depending on the region, excluding the LMC) which is evidenced by recent literature (Cleve et al, ; Padulo et al, ). The power calculations in this paper are limited to only six regions in the brain; however, it is logical to assume a similar behaviour in adjacent regions with similar spectra quality.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is an important finding for studies that hypothesise a low concentration change in GABA. However, for an effect size of around 15%, we predict much more reasonable sample sizes (between 8 and 43 depending on the region, excluding the LMC) which is evidenced by recent literature (Cleve et al, ; Padulo et al, ). The power calculations in this paper are limited to only six regions in the brain; however, it is logical to assume a similar behaviour in adjacent regions with similar spectra quality.…”
Section: Discussionsupporting
confidence: 74%
“…The number of subjects required to detect a 15% change of GABA concentration in each region of interest is reported in Table for each region, study design and duration investigated (assuming a standard voxel size of 27 cm 3 ). Here, we use 15% as an illustration based on a number of previous studies who have found a change in GABA in this range in response to intervention, for example (Cleve et al, ; Padulo et al, ). As expected it can be observed that for the same effect size, a larger number of subjects is required for between‐group studies compared to a within‐session study, and the longer the acquisition time, the fewer subjects that are needed.…”
Section: Resultsmentioning
confidence: 99%
“…The ACC and AI supported attentional control by deactivating the default mode network (Seeley et al ., ; Sridharan et al ., ). The vmPFC primarily compares sensory input to motivational states (Padulo et al ., ). Attentional control causes sustained phasic LC–NE activity that maintains alerting and orienting (Aston‐Jones & Cohen, ) and results in increased between‐network functional connectivity (Sara, ; Gilzenrat et al ., ; Mückschel et al ., ; Berry et al ., ).…”
Section: Attentional Functions and Networkmentioning
confidence: 97%
“…In depth, using spectra without water suppression, we determined the area of the water peak and utilized it as an internal standard reference for tCr quantification. [ 22 27 ]…”
Section: Methodsmentioning
confidence: 99%